2022
DOI: 10.1002/hsr2.467
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patterns of family support and its role on viral load suppression among youth living with HIV aged 15 to 24 years in southwestern Uganda

Abstract: Background Active family support helps as a buffer against adverse life events associated with antiretroviral therapy (ART) uptake and adherence. There is limited data available to explain how family support shapes and affects individual healthcare choices, decisions, experiences, and health outcomes among youth living with HIV (YLWH). We aimed to describe family support patterns and its role in viral load suppression among YLWH at a rural hospital in southwestern Uganda. Methods We performed a mixed‐method cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies have shown that PLWH with higher incomes were more likely to have family support compared to those with lower incomes [ 62 , 63 ]. This could be attributed to reduced economic insecurity and objective support among households with higher income [ 63 , 64 ], spotlighting a need for further attention to improve support systems among single and/or low-income PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PLWH with higher incomes were more likely to have family support compared to those with lower incomes [ 62 , 63 ]. This could be attributed to reduced economic insecurity and objective support among households with higher income [ 63 , 64 ], spotlighting a need for further attention to improve support systems among single and/or low-income PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…9 Within the context of social function, a crucial element is social support. 10 Furthermore, social support is associated with many health outcomes, such as ART adherence, 11 viral load suppression, 12 and anxiety and depression. 13 However, due to widely held misconceptions and stereotypes surrounding HIV, PLWH may encounter social discrimination and stigmatization, leading to a loss of social support and feelings of isolation.…”
Section: Introductionmentioning
confidence: 99%